2016
DOI: 10.1038/ncomms13661
|View full text |Cite
|
Sign up to set email alerts
|

Jarid2 binds mono-ubiquitylated H2A lysine 119 to mediate crosstalk between Polycomb complexes PRC1 and PRC2

Abstract: The Polycomb repressive complexes PRC1 and PRC2 play a central role in developmental gene regulation in multicellular organisms. PRC1 and PRC2 modify chromatin by catalysing histone H2A lysine 119 ubiquitylation (H2AK119u1), and H3 lysine 27 methylation (H3K27me3), respectively. Reciprocal crosstalk between these modifications is critical for the formation of stable Polycomb domains at target gene loci. While the molecular mechanism for recognition of H3K27me3 by PRC1 is well defined, the interaction of PRC2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
281
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(296 citation statements)
references
References 42 publications
14
281
1
Order By: Relevance
“…Surprisingly, they discovered a small but significant inhibitory effect of H2Aub on H3K27 trimethylation by PRC2 in vitro , which could not be readily explained. In a subsequent study, two additional protein components Jarid2–Aebp2 (Jumonji And AT-Rich Interaction Domain Containing 2-Adipocyte Enhancer-Binding Protein 2) were found to bind PRC2 and stimulate its activity ~25-fold on nucleosomes containing H2Aub (Figure 4) [50]. This confirmed the initially proposed crosstalk between PRC1 and PRC2, and indicated that its associated proteins modulate PRC2 function.…”
Section: Biochemical Crosstalk Between H2aub and H3k27me3supporting
confidence: 70%
“…Surprisingly, they discovered a small but significant inhibitory effect of H2Aub on H3K27 trimethylation by PRC2 in vitro , which could not be readily explained. In a subsequent study, two additional protein components Jarid2–Aebp2 (Jumonji And AT-Rich Interaction Domain Containing 2-Adipocyte Enhancer-Binding Protein 2) were found to bind PRC2 and stimulate its activity ~25-fold on nucleosomes containing H2Aub (Figure 4) [50]. This confirmed the initially proposed crosstalk between PRC1 and PRC2, and indicated that its associated proteins modulate PRC2 function.…”
Section: Biochemical Crosstalk Between H2aub and H3k27me3supporting
confidence: 70%
“…Indeed, Jarid2 may bind to PRC1-mediated H2AK119Ub, thus enabling PRC2 to become recruited. However, the situation may be complex, with multiple parallel pathways for PRC2 and PRC1 recruitment to the Xi 51 .…”
Section: Factors Associated With Prc1 and 2 Complexesmentioning
confidence: 99%
“…It is well established that the N-terminal domain of JARID2 is needed for its interaction with EZH2 and its recruitment to chromatin (Son et al, 2013;Kaneko et al, 2014a;Sanulli et al, 2015;Cooper et al, 2016;Chen et al, 2018). By contrast, the C-terminal of JARID2 has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%